Detection of α‐defensin in synovial fluids by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry as an innovative and cost‐effective assay for improved definition of periprosthetic joint infections. (14th May 2020) - Petrucca, Andrea; Santino, Iolanda; Gentile, Giovanna; Mazza, Daniele; Viglietta, Edoardo; Iorio, Raffaele; Simmaco, Maurizio; Ferretti, Andrea; Borro, Marina
Abstract : Rationale: Detection of α‐defensins in synovial fluid is gaining more and more interest in the field of correct diagnosis of periprosthetic joint infections (PJIs). At present, they can be assessed by a quantitative enzyme‐linked immunosorbent assay which is expensive and time‐consuming and by a qualitative lateral flow immunoassay which is rapid but quite expensive and whose clinical sensitivity is debated. Thus, developing an alternative rapid, accurate, and low‐cost assay for α‐defensins is important to make α‐defensins actionable as novel key clinical markers. Methods: Synovial fluid (SF) samples were obtained from 18 patients undergoing revision of primary joint arthroplasty. Of these, eight met the 2013 Musculoskeletal Infection Society (MSIS) criteria for PJIs, the remaining were classified as aseptic failure. Microbiological analysis and Synovasure assays were carried out on all samples. Sample preparation and the matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) mass spectrometry (MS) settings were adjusted to detect human neutrophil peptide (HNP)‐1, ‐2 and ‐3 and to obtain optimal results in term of sensitivity and stability. Results: MALDI‐TOF MS was able to detect HNPs in SF from septic patients. No signals for HNPs were detected in SF from aseptic failure. The limits of detection (LOD) were 2.5 and 1.25 μg/mL for HNP‐2 and HNP‐1, respectively. The turnaround time of the analysis is 20 min, and SF samples are stable at −20°C for up to 3 days. Assay sensitivity, specificity, and positive and negative predictive values (PPV and NPV) were 100% for all parameters. On the same SF samples, the Synovasure assay showed lower sensitivity specificity, and PPV and NPV of 87.5%, 90%, 87.5% and 90%, respectively. Microbiological analysis of SF confirmed the presence of bacteria only in SF MSIS‐positive patients. Conclusions: The reported MALDI‐TOF MS assay was able to detect and differentiate HNPs in SF samples and showed a slightly better diagnostic accuracy than the Synovasure assay.